Strengthening Local Wisdom Through the Application of Jawi Script at SMK YP. Abisatya Sarah School - Lubis, Rosliana; Rahimah, Rahimah; Ritonga, Parlaungan; Nasution, Latifah Yusri (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Jawi script is a Malay cultural heritage that reflects local wisdom and literacy traditions. However, its use is increasingly limited due to the lack of teaching resources and structured learning in schools. SMK YP. Abisatya Sarah School, as a vocational and culture-based institution, faces challenges in preserving this heritage among younger generations.Aims: This paper aims to describe a community service program conducted by lecturers from Universitas Sumatera Utara to strengthen local wisdom through the introduction and application of Jawi script for teachers and students at SMK YP. Abisatya Sarah School.Methods: The program applied a participatory approach involving teachers, students, and the school community. Activities included observation, coordination, socialization, intensive training in reading and writing Jawi script, interactive practice activities, and reflective discussions. Data were collected through observation, participant involvement, and documentation.Results: The results indicate an improvement in students’ ability to read and write basic Jawi script. Students actively participated in learning activities, and teachers gained new insights and teaching materials. Quantitatively, 78% of students (23 out of 30) were able to write at least five basic Jawi words correctly after the training. In addition, 87% of students (26 out of 30) successfully distinguished similar letter forms such as ba, ta, tsa, and nun.Conclusion: The program enhanced cultural literacy and motivated teachers and students to preserve Jawi script as part of local heritage, supporting quality education and the strengthening of cultural identity.